Disability in the perception of students. Results of research on attitudes toward people with disabilities - Beata Górnicka (Edukacyjna Analiza Transakcyjna)
The aim of the presented paper is to reveal selected results of research on the perception of people with disabilities and attitudes toward this group as declared by students from pedagogical and non-pedagogical fields of study.